Primary care system factors and clinical decision-making in patients that could have lung cancer: A vignette study in five balkan region countries - Petek Davorina; Assenova Radost; Foreva Gergana; Babić Svjetlana Gašparović; Šter Marija Petek; Prebil Nuša; Puia Aida; Smyrnakis Emmanouil; Harris Michael (Sciendo, 2022)
Lung cancer is the leading cause of cancer death, with wide variations in national survival rates. This study compares primary care system factors and primary care practitioners' (PCPs') clinical decision-making for a vignette of a patient that could have lung cancer in five Balkan region countries (Slovenia, Croatia, Bulgaria, Greece, Romania).